Penerapan Metode Weighted Aggregated Sum Product Assessment Dalam Pemilihan Peserta Olimpiade Sains - Matondang, Hasiholan; Situmorang, Dharma Bakti; Mesran, Mesran; Syahrizal, Muhammad (Bulletin of Data Science, 2024)
Science Olympiad participants will compete with other schools to show their abilities in the fields of science being contested, such as mathematics, physics, chemistry, biology and astronomy Or special themes chosen during the Olympics. This makes it difficult in the selection of participants for the Science Olympiad, because the Olympiad participants are proud and also carry the good name of the school that is studying, so that the wrong entry of participants causes problems in assessing school quality. In this study, the Science Olympiad participants were selected with the concept of a decision support algorithm using the WASPAS method. The WASPAS method, which stands for Weighted Aggregated Sum Product Assessment, is one of the methods used to minimize product defects by finding the highest and lowest values. The results of this study indicate that a student named Frans with a score of 8.7590 was selected to take part in the Science Olympiad as the best choice among the other options.